Celebrating the 10th Anniversary of the International Journal of Therapeutic Massage and Bodywork - Kennedy, LMT, BCTMB, DrPH, Ann Blair (International Journal of Therapeutic Massage & Bodywork, 2018)
From an informal conversation to a peer reviewed, open-access, indexed journal, we are now celebrating the 10th anniversary of the International Journal of Therapeutic Massage and Bodywork: Research, Education, and Practice. We celebrate the uniqueness of the Journal as the only fully open-access journal that addresses massage therapy and bodywork. Scholarly open-access journals have changed the face of scientific publishing in recent years: providing wider dissemination, allowing findings from taxpayer supported research to be available for free, and providing an avenue for researchers in the developing world to connect with researchers in developed countries. The editors of the Journal are regularly looking and soliciting articles from massage therapy researchers. This editorial describes the progress of the last ten years— from an article and readership standpoint—including changes in partnerships and increased visibility through social media.